Fostering global citizenship through faculty-led international programs - Mullens, Jo Beth; Cuper, Prudence H. (Emerald Publishing Limited : Information Age Publishing, 2012)
With awareness of both the opportunities and challenges presented by globalization, there is a growing trend among colleges and universities across the country to commit goals and resources to the concept of internationalizing their campuses. This can occur in a number of different ways but a common thread involves exploring the concept of global citizenship and finding ways to embed this concept in undergraduate curricula. For faculty, this may call for moving out of a presumed comfort zone in the traditional classroom and determining new approaches to teaching a generation of students who will live and work in a more global context. A method for accomplishing this work that is growing in popularity involves offering short-term, faculty-led field courses to international settings. In fact, today more college students are participating in such short-term study abroad opportunities than the more traditional semester and/or yearlong programs.Faculty and administrators who want to capitalize on short-term, study abroad programs as a means for internationalizing their campuses need practical resources to help them realize this challenging but important goal. They not only need support in developing the course curricula and logistics, but also in constructing authentic means for assessing the multi-faceted learning that occurs. Short-term international programs, when carefully planned and executed, engage the participants (both students and faculty) in unique learning experiences that can involve service, research, and critical analysis of what it truly means to be a global citizen. Such work helps define the somewhat nebulous but worthy goals of internationalizing campuses and fostering global citizenship.The authors of this text are professional educators with deep experience in global education and curriculum development. They offer a valuable resource for the development, execution and assessment of faculty-led international field courses that is at once theoretical, practical and motivational. Whether readers are considering offering an international field program for the first time and need guidance; are veteran field course leaders who would like to take their work to the next level; or are administrators attempting to encourage and provide needed support for faculty-led international programs, this book will prove invaluable.
Keywords: Foreign study.; International education.; College students -- Travel.; College teachers -- Travel.; Education -- Teaching -- Subjects -- General.; Teaching of a specific subject.; elektronické knihy; electronic books